Natural sulfur compounds in mental health and neurological disorders: insights from observational and intervention studies - Rana, Apeksha; Katiyar, Ashutosh; Arun, Alok; Berrios, Juan Negron; Kumar, Gaurav (Frontiers in Nutrition, 2025)
Over the years, the global disease burden of neurological disorders (NDs) and mental disorders (MDs) has significantly increased, making them one of the most critical concerns and challenges to human health. In pursuit of novel therapies against MD and ND, there has been a growing focus on nutrition and health. Dietary sulfur, primarily derived from various natural sources, plays a crucial role in numerous physiological processes, including brain function. This review offers an overview of the chemical composition of several natural sources of the sulfur-rich substances such as isothiocyanates, sulforaphane, glutathione, taurine, sulfated polysaccharides, allyl sulfides, and sulfur-containing amino acids, all of which have neuroprotective properties. A multitude of studies have documented that consuming foods that are high in sulfur enhances brain function by improving cognitive parameters and reduces the severity of neuropathology by exhibiting antioxidant and anti-inflammatory properties at the molecular level. In addition, the growing role of natural sulfur compounds in repairing endothelial dysfunction, compromising blood–brain barrier and improving cerebral blood flow, are documented here. Furthermore, this review covers the encouraging results of supplementing sulfur-rich diets in many animal models and clinical investigations, along with their molecular targets in MD, such as schizophrenia, depression, anxiety, bipolar disorder, and autism spectrum disorder, and ND, such as Alzheimer’s disease (AD), Parkinson’s disease (PD), Amyotrophic Lateral Sclerosis (ALS), and Multiple Sclerosis (MS). The prospects of natural sulfur compounds show great promise as they have potential applications in nutraceuticals, medicines, and functional foods to enhance brain function and prevent diseases. However, additional research is required to clarify the mechanisms by which it works, enhance its bioavailability, and evaluate its long-term safety for broad use.